Classic calligraphy for beginners : essential step-by-step techniques for copperplate and Spencerian scripts - Chung, Younghae (Quarry Books, 2022)
"Classic Calligraphy for Beginners is an introduction to traditional calligraphy that demonstrates the creative potential of various tools and how to apply them in a variety of ways to make learning Copperplate and Spencerian scripts easy and fun"--